The dynamics of marital relationship after infidelity: Phenomenological descriptive analysis on Muslim spouses - Alfaruqy, Muhammad Zulfa; Indrawati, Endang Sri (INSPIRA, 2023)
An unstable marital relationship, including an Islamic spouse, opens up opportunities for extramarital affairs. This study aimed to understand the dynamics of the relationship between a Muslim husband and wife who face a wife’s infidelity. This research uses qualitative methods with a phenomenological approach. The subject criterion is a Muslim wife who has had an affair and is still married. Three subjects were selected through a purposive sampling technique. Data collection using a semi-structured interview. The results show that the background of the wife’s infidelity is multi-factor. Marital relations reflect the interdependence of husband and wife. This relationship becomes more dynamic and complex because of the presence of a third person. During an affair, the relationship is under an actor’s control. The relationship transforms into a controlling partner after the affair. Wives initiate nonmutual relations manifested in permissive behavior towards husbands as an effort to atone for guilt and maintain a marriage. The research has theoretical implications for religion and supports the effect of social norms in reading the interdependence of marital relations between Islamic husband and wife.